Impact of removing point-of-sale tobacco displays on smoking behaviour among adolescents in Europe: a quasi-experimental study. Issue 4 (20th July 2018) - Van Hurck, Maureen M; Nuyts, Paulien A W; Monshouwer, Karin; Kunst, Anton E; Kuipers, Mirte A G
Abstract : Background: An increasing number of European countries implemented a point-of-sale (PoS) display ban on tobacco products. This study assessed the association between PoS display bans in Europe and adolescent smoking and perceived accessibility of tobacco, 2–6 years after PoS display ban implementation. Methods: In a quasi-experimental design, we compared individuals in countries that did and countries that did not implement a PoS display ban, before and after implementation. We used repeated cross-sectional data of 174 878 15-year-old and 16-year-old adolescents from 25 countries from the 2007, 2011 and 2015 European Survey Project on Alcohol and Other Drugs surveys. Multilevel logistic regression models examined smoking behaviour (regular smoking vs other) and perceived access (easy vs difficult) as a function of display ban implementation and controlled for survey year, gender, parental education and implementation of other tobacco control policies. Interaction with gender was tested. Results: The implementation of a PoS display ban was associated with a 15% larger drop in the odds of regular smoking (OR 0.85, 95% CI 0.79 to 0.91), but was not significantly associated with perceived accessibility of tobacco (OR 0.97, 95% CI 0.892 to 1.03). Associations were similar in males and females (cross-level interactions of gender with display ban were not statistically significant for either outcome). Conclusion: The implementation of PoS display bans in Europe was associated with a stronger decrease in regular smoking among adolescents. This decrease does not appear to be driven by a decreasing accessibility of tobacco, but might be caused by further de-normalisation of tobacco as a result of PoS display bans.